Bronchial asthma - a clinical study - Jayasinghe, K.S.A.; Wijesiriwardena, B.C.; Sheriff, M.H.R.; Dharmadasa, K. (Ceylon College of Physicians, 1983)
Abstract: One hundred adult patients with Bronchial Asthma were studied. The clinical pattern of asthma as seen in our adult asthmatic population is compared with other countries in the tropical and temperate zones. In the majority the disease started after the age of 20 years. Age of onset was earlier for females. Associated atopic diseases were not common. The main precipitating factors were rainy weather, upper respiratory tract infections, various food items and dusts High eosinophil Counts were common in the absence of Tropical pulmonary Eosinophilia. Right ventricular hypertrophy and failure was extremely rare.
Journal of the Ceylon College of Physicians; 1983; Vol: 16; 54-67p.